2023
DOI: 10.3390/ijerph20021419
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Cost over 12 Hospitalization Weeks of Postacute Care for Stroke

Abstract: Few studies have investigated changes in functional outcomes and economic burden in patients in the postacute care cerebrovascular disease (PAC-CVD) program. We, for the first time, retrospectively investigated changes in functional performance and the national health insurance (NHI) cost over 12 PAC-CVD hospitalization weeks and evaluated the therapeutic effects of the PAC-CVD program on the NHI cost. Specifically, the functional outcomes and NHI cost of 263 stroke patients in the PAC-CVD program were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Several studies have found that age is a factor influencing LOS in the PAC-CVD program, and our study yielded a similar finding; specifically, we discovered that LOS tends to be shorter for older patients than for younger patients [ 12 , 30 , 31 ]. Rehabilitation teams may have lower expectations regarding functional recovery in elderly patients.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Several studies have found that age is a factor influencing LOS in the PAC-CVD program, and our study yielded a similar finding; specifically, we discovered that LOS tends to be shorter for older patients than for younger patients [ 12 , 30 , 31 ]. Rehabilitation teams may have lower expectations regarding functional recovery in elderly patients.…”
Section: Discussionsupporting
confidence: 82%
“…The program enhances patients’ physical function and provides support for their return home or transfer to a long-term care institution. One study found that during 0–12 weeks of hospitalization in the PAC-CVD program, the functional performance of patients significantly improved [ 12 ]. However, longer hospitalization within the PAC-CVD program may result in community hospitals facing a shortage of PAC-CVD beds, which increases the wait time for beds or requires patients to be transferred to a hospital with available beds [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations